La escasa valoración de la lengua materna kichwa, incide en la identidad cultural de los niños y niñas que asisten al primer grado de educación general básica del centro educativo comunitario intercultural bilingüe Yaguarzongo de la comunidad Yukukapak, cantón Saraguro, provincia de Loja, periodo 2012-2013 - Sarango Paque, Luz Victoria (2015)
This thesis relates to: THE POOR ASSESSMENT OF MOTHER TONGUE KICHWA INCIDE IN CULTURAL IDENTITY OF CHILDREN / AS ATTENDING THE FIRST STAGE OF BASIC EDUCATION GENERAL INTERCULTURAL BILINGUAL EDUCATION CENTER COMMUNITY COMMUNITY Yaguarzongo YUKUKAPAK, CANTON SARAGURO, PROVINCE of Loja, PERIOD 2012-2013.El overall objective analyze whether the lack of appreciation of the native language Quechua, affects the cultural identity of the children who attend the school "Yaguarzongo"The research was descriptive, because it involves the systematic collection and presentation of data to get a clear idea of the poor development of the Kichwa native language and its impact on the loss of cultural identity.Scientific, deductive, inductive, descriptive, statistical and analytic-synthetic, survey instruments such as the teacher and parents, direct activities for children: methods was used for execution.The technique used was the survey, which allowed it to meet the problems of the two variables topic: the instruments used were direct activities to children / as to idenfy factors affecting the low valuation of the mother tongue and its influence on kichwa the research population.The results show that the low practice of parents and grandparents determining influence on the low valuation of the mother tongue, these results allow us to establish diriguidas concluciomes and recommendations to the teacher, school, parents and community, and so sesibilizarlos on the importance of maintaining our cultural roots.The most relevant conclucion that has deribado of research is the importance of invigorating the kichuwa mother tongue, to help co child population of indigenous peoples, who are affected by low rating